2015
DOI: 10.1111/1365-2656.12440
|View full text |Cite
|
Sign up to set email alerts
|

Reefscapes of fear: predation risk and reef hetero‐geneity interact to shape herbivore foraging behaviour

Abstract: Predators can exert strong direct and indirect effects on ecological communities by intimidating their prey. The nature of predation risk effects is often context dependent, but in some ecosystems these contingencies are often overlooked. Risk effects are often not uniform across landscapes or among species. Indeed, they can vary widely across gradients of habitat complexity and with different prey escape tactics. These context dependencies may be especially important for ecosystems such as coral reefs that va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
104
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(117 citation statements)
references
References 61 publications
13
104
0
Order By: Relevance
“…These observations indicate that our resource patches offered diminishing returns to herbivores, and, thus, quitting harvest rates scaled linearly with our recorded metric of individual average bite rate (Appendix S4: Fig. Our findings both reinforce and contrast recent work in the Florida Keys: Catano et al (2016) observed depressed herbivory and higher individual bite rates by herbivores in riskier habitat, but also showed that risk increased with structural complexity of the habitat. Consequently, the more than two-fold (1.22 bites/s) increase in individual average bite rate we observed between our within-reef (2 m in from reef edge) patch and our furthest patch from the refuge habitat of the reef (30 m away) largely reflects higher costs of predation (i.e., higher perceived predation risk by herbivores).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These observations indicate that our resource patches offered diminishing returns to herbivores, and, thus, quitting harvest rates scaled linearly with our recorded metric of individual average bite rate (Appendix S4: Fig. Our findings both reinforce and contrast recent work in the Florida Keys: Catano et al (2016) observed depressed herbivory and higher individual bite rates by herbivores in riskier habitat, but also showed that risk increased with structural complexity of the habitat. Consequently, the more than two-fold (1.22 bites/s) increase in individual average bite rate we observed between our within-reef (2 m in from reef edge) patch and our furthest patch from the refuge habitat of the reef (30 m away) largely reflects higher costs of predation (i.e., higher perceived predation risk by herbivores).…”
Section: Discussionsupporting
confidence: 85%
“…S5). This latter distinction likely reflects predominant predator hunting modes, with ambush predators (grouper) in the Keys (Catano et al 2016) but chase predators (reef sharks) in Mo'orea (Mourier et al 2012, 2013, Brooks 2016, and suggests that the features that drive landscapes of fear in reef fishes depend on the composition of the predator assemblage. In addition, we observed a significant, albeit weak, trend toward larger fish total length with increased distance from refuge; this could reflect diminishing predation risk, as prey movement speed (and, thus, escape potential) can increase with body size (Bejan and Marden 2006).…”
Section: Discussionmentioning
confidence: 99%
“…, Catano et al. ). It has also been argued that effective ecological restoration may depend on reestablishing landscapes of fear because fear may be as or more important than direct killing in structuring food webs and modifying ecosystem function (Manning et al.…”
Section: Discussionmentioning
confidence: 98%
“…In the presence of predators, prey will often modify their behaviors to balance the risk of mortality with the reward of accessing food, mates, or other resources (Catano et al., 2016; Sih, Cote, Evans, Fogarty, & Pruitt, 2012; Snell‐Rood, 2013). Prey may reduce their activity levels, utilize defenses, or seek refuge when they perceive the risk to be high (Lima & Dill, 1990; Lindberg, 1980).…”
Section: Discussionmentioning
confidence: 99%